Management strategies to improve beef feedlot performance and assessment of nutrient composition of beef retail cuts - Schutz, Jennifer Sue, author; Engle, Terry, advisor; Belk, Keith, committee member; Archibeque, Shawn, committee member; Van Campen, Hana, committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: beef; feedlot management; nutritive value; performance; purge; retail cut